Billboard multilingual online system (BMOS) - Mohd Hasnul Shahril, Harun (2010)
Billboard Multilingual Online System is a system that sends an instant update message about games in a stadium to other computer into various type of language. This system operates using switch and router to connect to another language billboard. The main computer which is the default language will be controlled by an administrator to send the update result of the game such as current score, current match time and home and name of the team in the game. This scoreboard system can translate language into another language simultaneously during the games event.